Organizational Factors Affecting Successful Implementation of Chatbots for Customer Service. Issue 1 (2nd January 2023) - Zhang, Juliana J. Y.; Følstad, Asbjørn; Bjørkli, Cato A.
Abstract: While chatbots have become an important part of customer service operations, there is a knowledge gap concerning organizational aspects of chatbot implementation and management. In response to this gap, we present a study of organizational factors affecting successful chatbot implementation. The study involved six organizations that had implemented chatbots for customer service within the last three years. Interviews were conducted with chatbot project owners, managers, developers, and customer service personnel – a total of 14 interviews. Through thematic analysis, five organizational factors were detailed as important for successful chatbot implementation: (1) work and team organization, (2) change management, (3) competencies and competency acquisition, (4) organizational resources, and (5) performance measures. We also present findings on the organizations' motivations and key success criteria for chatbot implementation. Based on the findings we summarize implications for theory and practice and point out directions for future research.